Aktualisasi Nilai Aswaja Nahdlatul Ulama dalam Mencegah Radikalisme - Muhammad Nu’man Nurridho; Salamah, Umi (Advances in Humanities and Contemporary Studies, 2021)
MTs Miftahul Huda Turen is one of the educational institutions that develops the NU Aswaja material by making it an educational curriculum that is expected to be able to counteract even negate the potential spread of radical religious understandings, especially among students. So, with the development of the Aswaja material, it attracted the attention of researchers to find out more about: 1) the potential for religious radicalism in MTs Miftahul Huda Turen; 2) actualization of NU Aswaja values ​​in MTs Miftahul Huda Turen. This research is a descriptive qualitative research, by taking the place of research in MTs Miftahul Huda Turen Malang. Data collection uses purposive sampling technique, namely research in a representative population. Data analysis is carried out by condensation of data, then presentation of data, and finally from the data that has been compiled is drawn conclusions. Checking the validity of the data is carried out with credibility which includes extension of participation, diligence in observation, triangulation and use of expert references. The results of the study show that: 1) the religious understanding aspects of teachers and students in MTs Miftahul Huda Turen are related to contemporary issues of radicalism such as intolerance, provocation in the name of religion, ethics of amar ma’ruf nahi munkar and jihad of the Khilâfah Islâmiyah and Islamic kâffah, shows the perspective and attitude that are inclusive, moderate and tolerant so that there is no potential for radicalism to be found; 2) actualization of NU Aswaja values ​​is realized in the form of curriculum and learning planning, learning implementation, and NU amaliah ritual activities. Aswaja NU values ​​are actualized well in MTs Miftahul Huda through understanding, habituation and exemplary methods, so students have a way of thinking and attitude that is tawassuth, tasâmuh and tawâzun.